2008
DOI: 10.1371/journal.ppat.1000245
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Neurotoxin Devoid of Receptor Binding Domain Translocates Active Protease

Abstract: Clostridium botulinum neurotoxin (BoNT) causes flaccid paralysis by disabling synaptic exocytosis. Intoxication requires the tri-modular protein to undergo conformational changes in response to pH and redox gradients across endosomes, leading to the formation of a protein-conducting channel. The ∼50 kDa light chain (LC) protease is translocated into the cytosol by the ∼100 kDa heavy chain (HC), which consists of two modules: the N-terminal translocation domain (TD) and the C-terminal Receptor Binding Domain (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
87
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(96 citation statements)
references
References 51 publications
8
87
0
1
Order By: Relevance
“…Therefore, what role, if any, does lipid composition play in channel formation by BoNTs? Interestingly, channel formation in planar bilayer systems employed either asolectin or defined lipid mixtures containing both phosphatidylserine and ganglioside GT1b (21,43). Thus, the requirement for acidic lipids in regulating the formation of the TeNT interfacial intermediate state may be a shared property among the CNTs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, what role, if any, does lipid composition play in channel formation by BoNTs? Interestingly, channel formation in planar bilayer systems employed either asolectin or defined lipid mixtures containing both phosphatidylserine and ganglioside GT1b (21,43). Thus, the requirement for acidic lipids in regulating the formation of the TeNT interfacial intermediate state may be a shared property among the CNTs.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the requirement for acidic lipids in regulating the formation of the TeNT interfacial intermediate state may be a shared property among the CNTs. Indeed, Fischer et al (21) previously noted that translocation activity of BoNT/A devoid of the receptor binding domain could not be observed in non-neuronal cell lines and speculated that membrane lipid composition might contribute to this effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that BoNT/A, in fact, possesses SNP-binding regions on both the H N and the H C domains (20,27). Employing dual detection of substrate proteolysis and single-channel currents, Fischer et al (21) showed that a protein consisting only of the L chain and the H N domain enabled passage of active protease into the cytosol of target cells. The H C domain appeared to be unnecessary for cell entry, channel action, or L-chain translocation, which suggested that each unit chaperones the others to attain toxicity (44).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies (20) using short (19-residue) overlapping peptides to map the synaptosome (SNP) binding regions on the H chain of BoNT/A showed that certain regions of the H N domain as well as the H C domain are capable of inhibiting BoNT binding to SNPs. Another study (21) reported that the L chain can be translocated efficiently by the H N domain alone in the absence of the H C domain. However, the precise role of the H N domain in membrane binding and insertion or channel formation is still unknown (22).…”
mentioning
confidence: 99%